Altered fine motor function at school age in Inuit children exposed to PCBs, methylmercury, and lead. (October 2016) - Boucher, Olivier; Muckle, Gina; Ayotte, Pierre; Dewailly, Eric; Jacobson, Sandra W.; Jacobson, Joseph L.
Abstract: Background: Motor deficits have frequently been reported in methylmercury (MeHg) poisoning in adults. However, whether exposure to neurotoxic contaminants from environmental sources early in life is associated with neuromotor impairments has received relatively little attention. This study examines the relation of developmental exposure to MeHg, polychlorinated biphenyls (PCBs), and lead to motor function in school-age Inuit children exposed through their traditional diet. Methods: In a prospective study in Nunavik, children (mean age = 11.3 years) were assessed on a battery of fine motor tasks, namely the Stanford-Binet Copying subtest ( N = 262), the Santa Ana Form Board, and the Finger Tapping Test ( N = 215). The relation of mercury (Hg; as an index of MeHg exposure), PCB congener 153 (PCB153), and lead concentrations in cord and current blood samples to task performance was examined using linear regression analyses. Results: After adjustment for potential confounders and control for the other contaminants, higher current PCB concentrations were associated with poorer Santa Ana Form Board and Finger Tapping performance. Results were virtually identical when PCB153 was replaced by other PCB congeners. Higher current Hg levels were independently associated with poorer Finger Tapping performance. Conclusions: This is the first prospective longitudinal study in children to provide evidence of neuromotor impairments associated with postnatal exposure to seafood contaminants from environmental sources. Fine motor speed appears particularly sensitive to the effects of postnatal PCB exposure, which is unusually high in this population. Results with postnatal MeHg are concordant with previous cross-sectional studies with children and adults. Highlights: Fine motor function was assessed in school-aged children from Nunavik. Postnatal PCBs were related to poorer manual dexterity and slower fine motor speed. Postnatal Hg exposure was independently associated with slower fine motor speed. There was no synergistic effect between the contaminants on motor outcomes.